2008
DOI: 10.1021/ja803524w
|View full text |Cite
|
Sign up to set email alerts
|

The Siderocalin/Enterobactin Interaction: A Link between Mammalian Immunity and Bacterial Iron Transport1

Abstract: The siderophore enterobactin (Ent) is produced by enteric bacteria to mediate iron uptake. Ent scavenges iron and is taken up by the bacteria as the highly stable ferric complex [FeIII(Ent)]3−. This complex is also a specific target of the mammalian innate immune system protein, Siderocalin (Scn), which acts as an anti-bacterial agent by specifically sequestering siderophores and their ferric complexes during infection. Recent literature suggesting that Scn may also be involved in cellular iron transport has i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 49 publications
7
105
0
3
Order By: Relevance
“…In fact, the LCN2:Ent:Fe 3+ complex is stable at pH 4.0, which implies that LCN2 can sequester Ent:Fe 3+ in most biological fluids, even acidified urine (8). Fe can only be released from the LCN2:Ent:Fe 3+ complex in acidified lysosomes, following the reduction of Fe and the proteolytic cleavage of LCN2 (42). Hence, LCN2 arrests extracellular bacterial growth by chelating Ent:Fe 3+ , limiting its bioavailability in solution (40,43,44).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the LCN2:Ent:Fe 3+ complex is stable at pH 4.0, which implies that LCN2 can sequester Ent:Fe 3+ in most biological fluids, even acidified urine (8). Fe can only be released from the LCN2:Ent:Fe 3+ complex in acidified lysosomes, following the reduction of Fe and the proteolytic cleavage of LCN2 (42). Hence, LCN2 arrests extracellular bacterial growth by chelating Ent:Fe 3+ , limiting its bioavailability in solution (40,43,44).…”
Section: Introductionmentioning
confidence: 99%
“…The general recognition mechanism of Scn has been extensively studied and is well understood (22,24,(27)(28)(29)(30)(31)(32)(33). Ligands bind in the highly sculpted protein calyx, where the key interaction is through an aryl group binding in a snug pocket between the side chains of K125 and K134, with electrostatic and cation-π interactions to this ring and neighboring ones mediated by the side chains of R81, K124, and K134 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 A-C) show clear electron density for the metal, but the only part of the hexadentate chelator that was resolvable is the catechol moiety binding in the K125/K134 pocket. Prior structural analyses had shown that [Fe III (Ent)] 3-is susceptible to backbone hydrolysis in the Scn calyx (27), but TRENCAM is nonhydrolyzable, so partial disordering of Ent or TRENCAM in these structures is likely accounted for by a combination of the inability of these tightly constrained chelators to fully coordinate ions larger than Fe 3+ , and the inability of the tightly constrained calyx to accommodate equatorial expansion of the metal-chelator complex. This latter property is consistent with the inability of Scn to accommodate salicylate-mode binding ferric siderophores (27), and explains the observation of an uncoordinated catechol group in the [Th IV (TRENCAM)] 2-complex structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The three calyx alanine substitutions were shown via circular dichroism (CD) to have little overall effect on mLcn2 structure (see Figure S6 in the Supporting Information), which is a conclusion supported by a crystallography study of hLcn2 with double mutations that included Arg103 in hLcn2. 7 In addition, the calyx mutants were evaluated for structural integrity by gel filtration and native polyacrylamide gel electrophoresis (see Figure S7 and Table S2 in the Supporting Information). These results show that, although there are differences between the mutants and WT proteins in the gel filtration elution profiles and in their rates of travel on electrophoresis, the differences are small and do not correlate with the ability of the aptamer to bind the protein.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%